Advances in Transition‐Metal Catalyzed Carbonylative Suzuki‐Miyaura Coupling Reaction: An Update. Issue 6 (9th February 2021) - Bhattacherjee, Dhananjay; Rahman, Matiur; Ghosh, Sumit; Bagdi, Avik Kumar; Zyryanov, Grigory V.; Chupakhin, Oleg N.; Das, Pralay; Hajra, Alakananda
Abstract: Transition metals have been an indispensable component of modern catalysis and among these palladium is the top‐ranked choice of chemists as a catalyst. After the several important developments of palladium catalysed C−C cross‐coupling reactions, carbonylative transformations have been realised as an attractive post modification of these reactions. Carbonylative Suzuki‐Miyaura coupling reaction is among such transformations for direct incorporation of CO fragment for the preparation of biaryl or aryl/alkyl ketones via transition‐metal catalysis. Ketone functionality is basically a valuable building block having huge pharmaceutical and agrochemical applications. Moreover, carbonylative Suzuki‐Miyaura coupling is also used in the synthesis of various natural bioactive molecules through the direct joining of molecular fragments via CO bridge. In this review, the past decade developments in the carbonylative Suzuki‐Miyaura coupling reactions are documented in detail with modern approaches in transition‐metal catalysis. Abstract :